Coproduction, public initiatives and service users’ motivation - Jakobsen, Morten; Thomsen, Mette Kjærgaard (Politica, 2015)
The quantity and quality of public services are improved when citizens coproduce, that is, contribute input to public service provision. It is therefore becoming increasingly common for local governments to initiative coproduction initiatives in order to enhance citizen input to coproduction. However, we know little about how these initiatives influence citizens’ motivation to coproduce. Using lower secondary education as the relevant service area, this study tests the effect of a coproduction initiative on parents’ intrinsic and extrinsic motivation. Our results show that only intrinsic motivation is positively and significantly related to citizen input to coproduction, and for less educated parents the initiative was found to have a negative effect on their intrinsic motivation. These results highlight how important it is that local governments pay attention to unintended motivation effects when they initiate coproduction initiatives.